Employing the Frontload Vocabulary Strategies in Enhancing Iraqi EFL Students’ Vocabulary Retrieval Abilities - misanjas, misanjas; Fakhir Jasim, Aswan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Vocabularies are the main elements of any language, thus, if there was not sufficient control in using them then the result would be a difficulty in vocabulary retrieval when needed. The frontload (pre teach) vocabulary strategies are used as a supportive pre learning strategies that help students to become acknowledged with the new materials that will be presented in the classroom. Applying these strategies can enable students remembering the vocabulary faster than traditional methods. The current study aims at investigating the effectiveness of using Frontload Vocabulary strategies in facilitating the Iraqi students’ vocabulary retrieval. In order to fulfill the aims of the study, the researcher adopted a questionnaire. The questionnaire contains 12 items with the five point scale (always, usually, sometimes, rarely, never).The participants of the study are Third-year students at the Department of English/ College of Education. The distribution of the questionnaire is done online, 35 students received the questionnaire and answered it. For the pilot study, fifteen students were selected in a random way; the result was that 30 minutes were required to finish the questionnaire items. The items of the questionnaire were worded in a clear and simple way. Therefore, the students did not face any difficulty in responding to the questionnaire items. The items of the questionnaire were divided into two parts even and odd to measure their reliability. The researcher employed the Pearson correlation formula to measure the questionnaire reliability; it has been found that the reliability is 0.754. Then the Spearman Brown formula is applied and the result was that the questionnaire reliability is 0.859 which reveals that the questionnaire is reliable and acceptable. Based on the outcome of the study, this strategy facilitate students to comprehend the text or passage because many students lack the motivation to continue reading a text or passage when they encounter a lot of unfamiliar vocabulary. Furthermore, it also has been found that this strategy helps the students to get prepared before the process of reading starts which makes their learning process much more effective.